2003
DOI: 10.1016/s0990-7440(02)00002-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated hypoxic shocks on growth and metabolism of turbot juveniles

Abstract: Turbot juveniles (45 g) were exposed for 41 d (17°C, 34‰ salinity) to constant normoxic (100-100% air saturation, 100-100) or moderate hypoxic (75-75% air saturation, 75-75) conditions and to repeated hypoxic shocks (20% saturation for 1 h, 5 d per week) from normoxic (100-20% air saturation, 100-20) or moderate hypoxic (75-20% air saturation, 75-20) conditions. A normoxic group was feed restricted (100-FR). Mass increase of 100-100 and 75-75 groups fed to satiation was not significantly different. In comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…It consists of faster fish growth following a period of growth depression as compared to their normally growing counterparts (Sevgili et al 2012). In fish, CG can be elicited through a number of ways such as starvation, feed restriction, exposure to low or high temperature and hypoxia (Eroldoğan et al 2006;Hayward et al 1997;Huang et al 2008;Miglavs and Jobling 1989;Person-Le Ruyet et al 2003). As observed in the present study, CG was more frequent with fish weight than fish length.…”
Section: Tag:st Ratiosupporting
confidence: 58%
“…It consists of faster fish growth following a period of growth depression as compared to their normally growing counterparts (Sevgili et al 2012). In fish, CG can be elicited through a number of ways such as starvation, feed restriction, exposure to low or high temperature and hypoxia (Eroldoğan et al 2006;Hayward et al 1997;Huang et al 2008;Miglavs and Jobling 1989;Person-Le Ruyet et al 2003). As observed in the present study, CG was more frequent with fish weight than fish length.…”
Section: Tag:st Ratiosupporting
confidence: 58%
“…5) and T 1.4 (Fig. 7), as well as results of the MWT algorithm applied to all sites and all years using lower threshold and shorter minimum event duration values (0.5 mg O 2 l −1 and 4 h; trigger duration 2 h) as justified in the "Introduction" (Rosenberg et al 1991;Sagasti et al 2001;Wu 2002;Person-LeRuyet et al 2003;Vaquer-Sunyer and Duarte 2008). Such more intense and shorter events occurred only at GB (18, 3, and 11 events in 2003GB (18, 3, and 11 events in , 2005GB (18, 3, and 11 events in , and 2006, respectively), MV (eight events in 2006), and NP (two and one event, in 2003 and 2006, respectively).…”
Section: Implications For Benthic Ecologymentioning
confidence: 94%
“…Taxonomic rankings indicate that fishes and crustaceans show greatest sensitivity, followed by echinoderms, while annelids and especially cnidarians and molluscs tend to show greatest tolerance (Diaz and Rosenberg 1995;Gray et al 2002;Vaquer-Sunyer and Duarte 2008). The highest risk of direct mortality occurs at concentrations of 0.5 to 1.0 mg O 2 l −1 for many moderately sensitive species and at 1.0 to 2.0 mg O 2 l −1 for many sensitive species, with mortality often taking place within the first 4 to 7 h; for highly tolerant benthic infaunal species, risk requires more severe conditions (≤0.5 mg O 2 l −1 ) of greater duration (days to weeks; Rosenberg et al 1991;Sagasti et al 2001;Wu 2002;Person-LeRuyet et al 2003;Vaquer-Sunyer and Duarte 2008). Larvae are generally more acutely sensitive than juveniles and adults (USEPA 2000); Rhode Island (RI) water quality regulations, designed for protection of larvae, treat a 1-day exposure to 2.9 mg O 2 l −1 as a violation (RIDEM 2006).…”
mentioning
confidence: 99%
“…However, it is unclear how these conditions might affect the growth and physiology of these fish because of the different methodologies used by previous authors, differences in the degree of hypoxia tolerance between species (Vanquer‐Sunyer & Duarte ) and the variable endpoints reported. Person‐Le Ruyet, Lacut, Le Bayon, Le Roux, Pichavant and Quéméner () exposed juvenile turbot [ Scophthalmus maximus (Waite 1910)] held under either normoxic (7.4 mg O 2 L −1 ) or moderate hypoxic (6.0 mg O 2 L −1 ) conditions to repeated hypoxic shocks (1.5 mg O 2 L −1 , 5 per week for 1 h) and showed significant reductions in growth (a 14.9% reduction in mass gain). Taylor and Miller () found that the growth rate of southern flounder [ Paralichthys lethostigma (Jordan & Gilbert 1884)] was reduced by 22.9% when they were exposed to episodic hypoxia (2.8–6.2 mg O 2 L −1 ) for 21 days.…”
Section: Introductionmentioning
confidence: 99%